Advances in Financial Risk Management Corporates, Intermediaries and Portfolios - Batten, Jonathan A.; MacKay, Peter; Mackay, P.; Wagner, N.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
The latest research on measuring, managing and pricing financial risk. Three broad perspectives are considered: financial risk in non-financial corporations; in financial intermediaries such as banks; and finally within the context of a portfolio of securities of different credit quality and marketability.
Keywords: Risk management; Business enterprises—Finance.; Corporations—Finance.; Investment banking; Securities; Macroeconomics; International economics; Risk Management; Business Finance; Corporate Finance; Investments and Securities; Macroeconomics/Monetary Economics//Financial Economics; International Economics